Therapy with vitamin D metabolits of structural and functional changes in bone tissue of working postmenopausal women with ostearcopenia - O. Ignatiev; M. Turchin; T. Ermolenko; O. Panyuta (Kazimierz Wielki University, 2022)
The prevalence of osteoporosis and vitamin D deficiency in postmenopausal women working under harmful labour conditions has been examined. Reduced bone mineral density was revealed in 85% of the persons under observation, the incidence of OP was 35%, sarcopenia (SP) - 35%. Vitamin D deficiency was found in 91.3% of the workers, at the same time severe VD deficiency was observed in 32.9%, VD deficiency - in 7.5%, and the optimal level of vitamin D was observed in 1.2% of cases. 79 PM women with OP aged 50 - 60 y. o. (mean age - (55.7 ± 0.9) years), working at harmful  conditions of the working environment with an average length of service 26.14 ± 0.91 years have been examined. Clinical group A (n = 30) received cholecalciferol at a dose of 2000 IU (4 drops) per day and alfacalcidol 1 μg (1 capsule) once a day for a year. This resulted in a positive effect on the level of 25(OH)D. The complex appointment of cholecalciferol and alfacalcidol reduced the level of PTH and confirmed the role of VD deficiency in the progress of secondary hyperparathyroidism. The data obtained revealed a slowing of the effect of VD on osteoclastogenesis. Decrease of bone resorption marker CTx in the women under examination confirmed the latter.